LEARNERS PERSPECTIVE: THE CONTRIBUTION OF PRE-LISTENING ACTIVITIES ON LEARNER’S LISTENING COMPREHENSION - Diana Diana; Evi Karlina Ambarwati; Praditya Putri Utami (PROJECT (Professional Journal of English Education), 2022)
The use of systematical learning activities is essential for the success of the learning process itself especially in acquiring second language skill such as listening. One of the most important part of listening learning is the preparation before the main listening task, it it important to implement pre-listening activities which has proven to be beneficial for the learner’s listening comprehension. The purpose of this study is to investigate the contribution of pre-listening activities on learner’s listening comprehension. This study was conducted in a form of qualitative method. The research data was taken from 20 English education students from a public university in Indonesia by using questionnaire in order to investigate learner’s perceptions on doing pre-listening activities and the impact on their listening comprehension. The result shows that the majority of learners agree that pre-listening activities activates their background knowledge which help them improve their listening comprehension. Thus, it can be concluded that pre-listening is important in facilitating listening acquisition in EFL post-secondary classroom. Keywords:  Listening, Pre-Listening, Comprehension